Transcranial Magnetic Stimulation-Induced Plasticity Mechanisms: TMS-Related Gene Expression and Morphology Changes in a Human Neuron-Like Cell Model - Thomson, Alix C.; Kenis, Gunter; Tielens, Sylvia; de Graaf, Tom A.; Schuhmann, Teresa; Rutten, Bart P.F.; Sack, Alexander T. (Frontiers in Molecular Neuroscience, 2020)
Transcranial Magnetic Stimulation (TMS) is a form of non-invasive brain stimulation, used to alter cortical excitability both in research and clinical applications. The intermittent and continuous Theta Burst Stimulation (iTBS and cTBS) protocols have been shown to induce opposite after-effects on human cortex excitability. Animal studies have implicated synaptic plasticity mechanisms long-term potentiation (LTP, for iTBS) and depression (LTD, for cTBS). However, the neural basis of TMS effects has not yet been studied in human neuronal cells, in particular at the level of gene expression and synaptogenesis. To investigate responses to TBS in living human neurons, we differentiated human SH-SY5Y cells towards a mature neural phenotype, and stimulated them with iTBS, cTBS, or sham (placebo) TBS. Changes in a) mRNA expression of a set of target genes (previously associated with synaptic plasticity), and b) morphological parameters of neurite outgrowth following TBS were quantified. We found no general effects of stimulation condition or time on gene expression, though we did observe a significantly enhanced expression of plasticity genes NTRK2 and MAPK9 24 hours after iTBS as compared to sham TBS. This specific effect provides unique support for the widely assumed plasticity mechanisms underlying iTBS effects on human cortex excitability. In addition to this protocol-specific increase in plasticity gene expression 24 hours after iTBS stimulation, we establish the feasibility of stimulating living human neuron with TBS, and the importance of moving to more complex human in vitro models to understand the underlying plasticity mechanisms of TBS stimulation.